Improving Students' Vocabulary Mastery and Listening Skills Using Bilingual Posters Translated Lyrics - Nur Rohman, Ana Bela Safitri; Sujatmiko, Sujatmiko (JEdu: Journal of English Education, 2024)
This research aims to: 1) To know the translation techniques used in translating the songs "Count on Me" and "History". 2) To describe the bilingual poster media to improve students' vocabulary mastery and listening skills. This research type is classroom action research. Data collection used observation, interviews, tests, and documentation. Data analysis uses Miles and Huberman's theory to analyze interview data. Test data can be analyzed using calculations. This research was conducted at SMPN 2 Sewon. The result of the song translation technique is that the translation technique that is often used is established equivalent with a total of 95,15%. Meanwhile, techniques that are rarely used in the song are pure borrowing and naturalized borrowing with a total of 0,88%. The results of classroom action research showed that there was an increase in students' vocabulary mastery and listening skills after using bilingual poster media. In the pre-test, there were only 18,75% of students who passed KKM. In post-test I, there was only 40,62% who passed. Then in post-test II, there were 84,37% of students passed the KKM, the results of post-test II had reached the success criteria so this research stopped in cycle II. In addition, this is also supported by the results of interviews and observations where most students feel helped to learn English using bilingual posters which can be seen from the enthusiasm of students during the learning process. Therefore, bilingual posters can enhance the vocabulary mastery and listening skills of students at SMPN 2 Sewon